3D mesoporous reduced graphene oxide with remarkable supercapacitive performance. (July 2019) - Jha, Plawan Kumar; Gupta, Kriti; Debnath, Anil Krishna; Rana, Shammi; Sharma, Rajendrakumar; Ballav, Nirmalya
Abstract: Chemical reduction of graphene oxide (GO) to reduced graphene oxide (rGO) is an important process in view of the development of graphene-based supercapacitors on industrial level. We report an in situ chemical reduction of GO by copper(I) salt (CuCl) and isolation of semiconducting rGO material with three-dimensional (3D) mesoporous structure. Fabricated all-solid-state supercapacitors of our rGO exhibited specific capacitance and energy density values as high as 310 F/g at a current density of 1 A/g and 10 Wh/kg, respectively in an eco-friendly aqueous gel polymer electrolyte (GPE) system. Furthermore, increasing the mass loading of rGO boosted the areal capacitance to a record value of about 580 mF/cm 2 at 1 mA/cm 2 current density. More than 80% capacitance was retained beyond 100, 000 continued charge-discharge (CD) cycles. Also, sustainability of our rGO supercapacitor over switching current densities in the CD cycles was excellent resembling the rate performance in battery-like energy storing devices. The use of organic electrolyte boosted the energy density of rGO to very high level of ∼22 Wh/kg. Graphical abstract: Image 1